A Design for the Dual Skin Paddle Circumflex Scapular Artery Perforator Flap for the Reconstruction of Complex Soft-Tissue Defects in Children: Anatomical Study and Clinical Applications. Issue 4 (October 2019) - Qing, Liming; Wu, Panfeng; Zhou, Zhengbing; Yu, Fang; Tang, Maolin; Tang, Juyu
Abstract : Background: The main drawbacks of the use of the circumflex scapular artery perforator (CSAP) flap for complex soft-tissue defect repair are the limitation of skin paddle size, which can be harvested to allow precise wound coverage and primary closure of the donor site. We developed a variant of the dual skin paddle CSAP flap to extend its applications and minimize donor-site morbidity when reconstructing complex soft-tissue defects in children. Methods: A detailed anatomical investigation of circumflex scapular artery (CSA) branches was conducted using a standardized injection of lead oxide in 25 fresh cadavers. Dual skin paddle CSAP flaps were harvested for the reconstruction of complex defects in the extremities in 16 children. Three types of dual skin paddle CSAP flap were used in this study: transverse chain-shaped, oblique chain-shaped, and trefoil-shaped flaps. Results: Three CSA branching patterns with superior branch diameters were observed: 34% of CSAs were of the transverse branch dominant type, 54% were of the descending branch dominant type, and 12% were of the codominant type. Sixteen dual skin paddle CSAP flaps were elevated successfully; they were of the transverse chain-shaped type in 2 cases, the oblique chain-shaped type in 9 cases, and the trefoil-shaped type in 5 cases. All flaps survived postoperatively. Primary closure of the donor site was achieved in all cases. Conclusions: The CSA system is an appropriate source for harvesting dual skin paddle CASP flap. Use of this flap for the reconstruction of complex soft-tissue defects in the extremities in children is an alternative approach that reduces morbidity and improves the cosmetic outcome at the donor site. Abstract : Supplemental digital content is available in the text.